Unfunded pension systems ageing and variance - Uebelmesser, Silke (Emerald, 2004)
Pension systems in most industrialised countries are unfunded, i.e. they are pay-as-you-go financed and thus depend on a well-balanced ratio (old) recipients to (young) contributors. This so-called dependency ratio will worsen significantly in the next few decades due to two developments: ageing of the population and increased labour mobility. This book analyses the viability of unfunded pension systems in the presence of the projected demographic evolution. The analysis focuses on questions concerning: efficiency considerations and the possibility of welfare improvements; political economy aspects and the feasibility of reforms, and; the process of European integration and its influence on national pension systems. The theoretical analysis is complemented in numerous ways by quantitative parts and institutional details. The consequences of the demographic crisis for the distribution of the pension burden within and across generations and in an international context are illustrated with respect to the specific situation in Germany and other European countries. It is shown for different settings of political power distribution and for different degrees of mobility what would happen without any reforms and what could and should be done to guarantee the survival of old-age security based on a fair sharing of the pension burden. Neither explosion nor erosion is the inevitable fate of unfunded pension systems. But to avoid either happening, fundamental reforms are necessary as soon as possible which loosen at least partially the intergenerational dependencies and thus reduce the pressure from the changing population structure on old-age security.
Keywords: Business & Economics -- International -- Economics.; Politics & government.; Welfare & benefit systems.; Pensions.; Old age pensions.; elektronické knihy; electronic books